Engaging Italy : American Women's Utopian Visions and Transnational Networks. - Madden, Etta M. (State University of New York Press, 2022)
Traces literary and social connections among three American women navigating the changing political landscape of 1860s and '70s Italy.
Keywords: Women -- Italy -- History -- 19th century.; Americans -- Italy -- History -- 19th century.; Italy -- Politics and government -- 1849-1870.; Italie -- Politique et gouvernement -- 1849-1870.; Femmes -- Italie -- Histoire -- 19e siècle.; Americans; Politics and government; Women; Italy; 1800-1899; History